2008
DOI: 10.1002/hep.22131
|View full text |Cite
|
Sign up to set email alerts
|

The cyclophilin inhibitor Debio-025 shows potent anti–hepatitis C effect in patients coinfected with hepatitis C and human immunodeficiency virus

Abstract: Debio-025 is an oral cyclophilin (Cyp) inhibitor with potent anti-hepatitis C virus activity in vitro. Its effect on viral load as well as its influence on intracellular Cyp levels was investigated in a randomized, double-blind, placebo-controlled study. Mean hepatitis C viral load decreased significantly by 3.6 log 10 after a 14-day oral treatment with 1200 mg twice daily (P < 0.0001) with an effect against the 3 genotypes (1, 3, and 4) represented in the study. In addition, the absence of viral rebound durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(190 citation statements)
references
References 18 publications
4
183
0
3
Order By: Relevance
“…These results provided for the first time a molecular mechanism for the early-on observed anti-HCV activity of CsA (18 -20). Although this initial report suggests that only CypB would be involved in the HCV replication proc-ess (17), a growing number of studies have recently pointed out a role for other cyclophilins (21)(22)(23)(24)(25).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 98%
“…These results provided for the first time a molecular mechanism for the early-on observed anti-HCV activity of CsA (18 -20). Although this initial report suggests that only CypB would be involved in the HCV replication proc-ess (17), a growing number of studies have recently pointed out a role for other cyclophilins (21)(22)(23)(24)(25).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 98%
“…Both of these mechanisms are independent of the well-established immunosuppressive action of cyclosporine. Nonimmunosuppressive cyclophilin inhibitors that bind to CypA and CypD are in human trials as treatments for hepatitis C infection (43). Future studies will be needed to confirm that these agents inhibit acetaminophen-induced liver injury, but the absence of immunosuppression has the potential to improve the drug's risk/benefit profile by reducing the risk for sepsis in these critically ill patients.…”
Section: Figurementioning
confidence: 99%
“…During a 15-d phase Ib study in which subjects coinfected with HIV and HCV received 1200 mg BID of Debio 025 or placebo, and Debio 025 resulted in a mean decrease in the viral load of 3.6 log 10 IU/ml (Flisiak et al, 2008b). In contrast, a phase I trial of Debio 025 suggested that the drug has a limited effect on HIV-1 replication.…”
Section: Debio 025 (Alisporivir)mentioning
confidence: 99%